Comparison of three different brushing techniques to isolate and culture primary nasal epithelial cells from human subjects. (1st September 2014) - Stokes, Andrea B.; Kieninger, Elisabeth; Schögler, Aline; Kopf, Brigitte S.; Casaulta, Carmen; Geiser, Thomas; Regamey, Nicolas; Alves, Marco P.
ABSTRACT: Purpose: Primary nasal epithelial cells are used for diagnostic purposes in clinical routine and have been shown to be good surrogate models for bronchial epithelial cells in studies of airway inflammation and remodeling. We aimed at comparing different instruments allowing isolation of nasal epithelial cells. Methods : Primary airway epithelial cell cultures were established using cells acquired from the inferior surface of the middle turbinate of both nostrils. Three different instruments to isolate nasal cells were used: homemade cytology brush, nasal swab, and curette. Cell count, viability, time until a confluent cell layer was reached, and success rate in establishing cell cultures were evaluated. A standard numeric pain intensity scale was used to assess the acceptability of each instrument. Results : Sixty healthy adults (median with interquartile range [IQR] age of 31 [26–37] years) participated in the study. Higher number of cells (×10 5 cells/ml) was obtained using brushes (9.8 [5.9–33.5]) compared to swabs (2.4 [1.5–3.9], p < 0.0001) and curettes (5.5 [4.4–6.9], p < 0.01). Cell viability was similar between groups. Cells obtained by brushes had the fastest growth rate, and the success rate in establishing primary cell cultures was highest with brushes (90% vs. 65% for swabs and 70% for curettes). Pain was highest with curettes (VAS score 4.0 [3.0–5.0] out of 10). The epithelial phenotype of the cultures was confirmed through cytokeratin and E-cadherin staining. Conclusions : All three types of instruments allow collection and growth of human nasal epithelial cells with good acceptability to study participants. The most efficient instrument is the nasal brush.